2008
DOI: 10.1080/17435390802018378
|View full text |Cite
|
Sign up to set email alerts
|

Not ready to use – overcoming pitfalls when dispersing nanoparticles in physiological media

Abstract: Industrial nanoparticles are not developed to be compatible with in vitro cell culture assays which are carried out in isotonic solutions at physiological pH and often in the presence of proteins. The tendency of nanoparticles to deagglomerate or agglomerate is strongly sensitive to these parameters. The state of agglomeration and the protein corona bear an important influence on the level of toxic effects via the change of transport mechanisms and surface coating. Here we rigorously characterized the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 154 publications
(159 citation statements)
references
References 24 publications
8
148
1
2
Order By: Relevance
“…Dispersion of nanoparticles in protein solution can drastically alter the dispersion characteristics, leading to either increased or decreased particle sizes. We have previously demonstrated that the addition of Fetal Calf Serum leads to deagglomeration [1] and hence to smaller particle sizes for some of the particles tested here. Also, it could be demonstrated by Ehrenberg and coworkers that particles coated with serum proteins adsorbed onto endothelial cells in higher amounts as uncoated ones [2].…”
Section: Introductionmentioning
confidence: 99%
“…Dispersion of nanoparticles in protein solution can drastically alter the dispersion characteristics, leading to either increased or decreased particle sizes. We have previously demonstrated that the addition of Fetal Calf Serum leads to deagglomeration [1] and hence to smaller particle sizes for some of the particles tested here. Also, it could be demonstrated by Ehrenberg and coworkers that particles coated with serum proteins adsorbed onto endothelial cells in higher amounts as uncoated ones [2].…”
Section: Introductionmentioning
confidence: 99%
“…Be sure to exclude interferences of the NM with the assay ( see Subheading 3.6.1 ). Sterility of NM powders or suspensions can be achieved by autoclaving [ 22 , 29 ], γ-irradiation [ 30 ], or possibly fi ltration. However, one has to verify that these processes do not change NM properties or concentration.…”
Section: Sterilitymentioning
confidence: 99%
“…However, one has to verify that these processes do not change NM properties or concentration. We have previously used X-ray photoelectron spectroscopy (XPS) to verify that γ-irradiation did not change the surface properties of diverse NM [ 30 ].…”
Section: Sterilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomaterials are by no means "ready to use" in biological testing [2], thus they must be accurately characterized and tested under the conditions they are used in biological assays. As an example, data are often incomplete regarding the properties of nanomaterials upon contact with biological systems [3][4][5].…”
Section: The Need For Complete Data Reportingmentioning
confidence: 99%